Impact of Capillary End Effect during Displacement in Layered-Heterogeneous Formations - Mammadova, Ye.V. (Herald of Azerbaijan Engineering Academy, 2023)
The oil fields of Azerbaijan are mainly characterized by stratification of reservoirs with heterogeneous permeability. This is the reason for the rapid rate of water cut, the formation of residual unrecoverable reserves in low-permeability reservoir zones, and a decrease in the rate of production. The article considers the determination of the average value of phase permeabilities for layers with a drop in the value of permeability with depth. In this case, water evenly moves from the upper layers to the lower ones. The described method is generalized and is effectively applied under the condition that the corresponding end points of the relative phase permeability curves will change from layer to layer.